The Motif of Singing in “The Meek One” - Valentina S. Sergeeva (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
The article traces the connection between F.M. Dostoevsky’s works and the Gnostic worldview with reference to the general acquaintance of the 19th century readers with Gnostic sources, through the example of “The Meek One”. This paper is an attempt to interpret the story’s climax (the protagonist’s singing and suicide) through the prism of the treatise Pistis Sophia that entered scientific circulation in the end of the 18th century and became one of the most talked-about samples of the early mystic literature.